Physiological parameters to select upland rice genotypes for tolerance to water deficit - Guimarães, Cleber Morais; Stone, Luis Fernando; Castro, Adriano Pereira de; Morais Júnior, Odilon Peixoto de (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the feasibility of using physiological parameters for water deficit tolerance, as an auxiliary method for selection of upland rice genotypes. Two experiments – with or without water deficit – were carried out in Porangatu, in the state of Goiás, Brazil; the water deficit experiment received about half of irrigation that was applied to the well‑watered experiment. Four genotypes with different tolerance levels to water stress were evaluated. The UPLRI 7, B6144F‑MR‑6‑0‑0, and IR80312‑6‑B‑3‑2‑B genotypes, under water stress conditions, during the day, showed lower stomatal diffusive resistance, higher leaf water potential, and lower leaf temperature than the control. These genotypes showed the highest grain yields under water stress conditions, which were 534, 601, and 636 kg ha-1, respectively, and did not differ significantly among them. They also showed lower drought susceptibility index than the other genotypes. 'BRS Soberana' (susceptible control) was totally unproductive under drought conditions. Leaf temperature is a easy‑read parameter correlated to plant‑water status, viable for selecting rice genotypes for water deficit tolerance.